Effects of stocking density on survival, growth and production of Thai climbing perch (Anabas testudineus) under fed ponds (Kesan ketumpatan penstokan kepada kemandirian, pertumbuhan dan penghasilan ikan puyu - Khatune-Jannat, Most.; Rahman, Mohammad Mustafizur; Bashar, Md. Abul; Hasan, Md. Nahid; Ahamed, Ferdous; Hossain, Md. Yeamin (Penerbit UKM, 2012)

(untitled)
An experiment was carried out in 6 earthen ponds to investigate the effects of stocking density on growth, survival and production of Thai climbing perch (Anabas testudineus). Three stocking densities (treatments) were compared: ponds with 350, 400 and 550 individuals per decimal (0.01 acre). All treatments were randomly assigned and in duplicate. Artificial feed containing 34% crude protein was applied initially 20% of total fish weight per day. Gradually the feeding rate was reduced to 15, 12, 10, 8 and 5% of total fish weight per day. Feeding rates per pond were adjusted fortnightly after weighing minimum 20% of the fish stocked. The duration of the experiment was 90 days. Results showed that all growth parameters were higher in ponds with lower stocking density than the ponds with higher stocking density, while total fish yield was higher in ponds with higher stocking density than in the ponds with lower stocking density. Cost-benefit analysis revealed that all three systems were economically profitable. However, the ponds with a stocking density of 550 individuals per decimal were the most profitable system. More research is still needed to further optimize stocking density of Thai climbing perch in aquaculture ponds. Until then, stocking 550 individuals of Thai climbing perch per decimal will yield a good production to fish farmers in the South and South-East Asian regions.